O trabalho dos assistentes sociais nos hospitais universitários Onofre Lopes (HUOL) e Hospital Ana Bezerra (HUAB) da UFRN: os desafios da formação permanente - Barros, Rose Marie de Araujo (2012)
This paper discusses the process of training social workers in the environment of University Hospitals- UH s. These hospitals provide space for professional education aiming to achieve a critical and purposeful professional performance. As environments for training, producing knowledge and providing essential services to the public, these hospitals require all members of the healthcare team to have a continued education. Understanding that training has to be a priority and conceived as constant pursuit for update through the interaction of Teaching, Researching and EPO ( Education and Public Outreach). These dimensions provide approximations and domain of theoretical and methodological, giving special importance to understanding the social reality, a sine qua non condition to the work of the Social Service professional. The main goal of the research was to comprehend how the continuous professional education of the social worker occurs and it s relation with the articulations involving Teaching, Researching and EPO, as significant elements for the job of the social workers in the Hospital Universitário Ana Bezerra and Hospital Universitário Onofre Lopes/UFRN. The research was conducted through a literature review, documentary and field inquiries with semistructured interviews including the group of 09 (nine) social workers from the aforementioned hospitals, taking as a reference the quantitative and qualitative approach to analyze mediations that stand between the subject and the social context. The results indicate that social workers in these university hospitals have their insertion beyond the care provided to patients in performance in the areas of education through preceptorship to undergraduate students and social work residents in and extension projects with low insertion in area of research. We note that there is a recognition of the importance of a continuous education, indicating that the qualification of social worker is essential in transforming their daily professional practice to better monitor, critically explain the peculiarities of public health in its everyday showing of how unequally access is provided to the users of the public health system